What is the role of teams in knowledge management? Some indications from practice. (19th April 2004) - Becker, Markus C.
It is argued that, when it comes to knowledge management, the attention of managers and researchers alike is still focused on IT, sidelining other important aspects of knowledge management. One important sidelined aspect is the role of teams and groups for storing, retrieving, sharing, creating and utilising knowledge. Empirical research in customer service centres shows that managers are not aware of the knowledge-related functions of teams, while team members are. This neglect on the part of managers is reflected in the literature, where only a few papers point out the important role of teams in knowledge management processes. This diagnosis has wider-ranging implications it fields the hypothesis that teams are crucial for integrating knowledge. Interaction between team members is central and therefore should be supported by managers.